Exploring brand preference and its spatial patterns in the Chinese automobile market. Issue 2 (3rd July 2018) - Liu, Zhimin; Song, Wei; Liu, Daqian; Lu, Jia
ABSTRACT: China has remained the world's largest new-automobile market, where personal vehicles play an increasingly important role in people's daily lives. Using automobile sales volumes for 337 prefecture-level cities from the Economic Advisory Centre of the State Information Centre, this study examined automobile brand preference and its spatial variation in China. The market shares of automobile brands and revealed comparative advantages in city markets were analysed, and geographical patterns were explored using spatial statistics. Analytical results revealed apparent regional heterogeneity and spatial concentration in automobile brand preference across China's automobile market.